SIMULASI PENGATURAN KECEPATAN MOTOR INDUKSI 3 PHASA DENGAN DIRECT TORQUE CONTROL MENGGUNAKAN MATLAB - Khasanah, Ulfatun; Supari, Supari; Heranurweni, Sri (Elektrika, 2017)
Induction motors are widely used in the industrial world because they have many advantages, including construction that is very simple and strong, cheap, has high efficiency, quite good power factor, and maintenance is easier. Besides the advantages of induction motors also have weaknesses, one of the disadvantages of an induction motor is not being able to maintain its speed constantly if there is a change in load. If there is a change in load, the speed of the induction motor will decrease. One method of regulating the speed of an induction motor developed in addition to vector control is the Direct Torque Control (DTC) method. The DTC control technique allows direct and separate flux and torque settings and can be done without using a speed sensor. The estimated rotor rotation, torque and flux is carried out by the DTC which is inputted with stator voltage and current. To achieve the desired flux and torque estimation is used as feedback on the control system. In this final assignment, the speed regulation of the induction motor will be simulated using the DTC method using Matlab. The results obtained through the simulation show the length of time to reach the reference speed for speeds of 500rpm and 1000 rpm is around 0.5 seconds. Keywords : Induction motor, Direct Torque Control, Matlab.